NEW MASCULINITIES MOVEMENT FOR GENDER EQUALITY: THE ROLE OF MEN TO ACHIEVING SDGS - Pamungkas, Martinus Danang; Ningtiyas, Luluk Ayu (Global and Policy Journal of International Relations, 2023)
This research examines and identifies men's role in supporting the SDGs' achievement. This research uses the literature study method. Data from literature relevant to the research title, such as books, journal articles, reports, and website articles, will be analyzed qualitatively. Gender inequality has become a particular concern globally, especially regarding human resource development. Gender inequality appears in marginalization, subordination, stigma, stereotypes, and violence. The root of the problem of gender inequality is the patriarchal social system that does not support women. Men play a strategic position in supporting women to change social norms, structures, and policies that disadvantage women. We argue that to achieve gender equality and women's empowerment, there is a need to stabilize the discourse of men's roles by abandoning traditional hegemonic masculinity values towards a new masculinity movement that supports gender equality. This research implies that the deconstruction of a new masculinity that mediates the role of men in sustainable development, especially in the social, economic, political, and domestic sectors, in encouraging the realization of gender equality is critical, so we recommend policies from the government and related sector institutions. Keywords: new masculinities, movement, gender equality, SDGsDOI: https://doi.org/10.33005/jgp.v11i02.4160